A digger at home and abroad - Denny, W. J. (William Joseph) (Melbourne : Popular Publications, 1941)
The sketches describe impressions and experiences on war service, as well as comments on military, legal, political, literary and social questions.
Dornbusch, C.E. Australian military bibliography
Keywords: Denny, W. J; Soldiers -- Australia -- Biography; World War, 1939-1945 -- Personal narratives, Australian; World politics -- 20th century